A pathogen imprinted hybrid polymer capacitive sensor for selective Escherichia coli detection - Mugo, Samuel; Lu, Weihao; Dhanjai, Dhanjai (My University, 2020)
A versatile pathogen imprinted polymer electrochemical sensor has been developed for Escherichia coli detection. The sensor is based on layer by layer assembly of multi-walled carbon nanotubes (CNT), nanocellulose (CNC) films, integrated with polyaniline (PANI) doped phenylboronic acid (PBA). The sensing layer is a poly(methacrylic acid) based pathogen microcontact imprinted polymer (PIP). The PIP@PBA/PANI@CNT/CNC sensor exhibits a high affinity towards E. coli in real biological matrices, while effective in discriminating E. coli amidst other bacteria. Using capacitance and impedance as transduction methods, the PIP sensor recorded a low limit of E. coli detection of 8.7 ± 0.5 cfu/ml, with a rapid response of ≤5 min.
Keywords: cell imprinted polymers; E. coli capacitive sensor; pathogen imprinted polymers